Tuberculosis-Infected Giant Bulla Treated by Percutaneous Drainage Followed by Obliteration of the Pulmonary Cavity Using Talc: Case Report - Heo, Jeongwon; Bak, So Hyeon; Ryu, Se Min; Hong, Yoonki (Journal of chest surgery, 2021)
Tuberculosis (TB)-infected giant bullae are rare. A 55-year-old man was referred when an infected bulla did not respond to empirical treatment. Computed tomography showed a giant bulla in the right upper lobe with an air-fluid level and surrounding infiltrate. Sputum culture, acid-fast bacilli (AFB) stain, and polymerase chain reaction (PCR) for TB were negative. Percutaneous drainage of the bullous fluid was performed. AFB stain and PCR were positive in the drained fluid. The patient was given anti-TB drugs and later underwent obliteration of the pulmonary cavity using talc. To summarize, we report a patient with a TB-infected giant bulla that was treated successfully with anti-TB drugs and obliteration of the pulmonary cavity using talc.Tuberculosis (TB)-infected giant bullae are rare. A 55-year-old man was referred when an infected bulla did not respond to empirical treatment. Computed tomography showed a giant bulla in the right upper lobe with an air-fluid level and surrounding infiltrate. Sputum culture, acid-fast bacilli (AFB) stain, and polymerase chain reaction (PCR) for TB were negative. Percutaneous drainage of the bullous fluid was performed. AFB stain and PCR were positive in the drained fluid. The patient was given anti-TB drugs and later underwent obliteration of the pulmonary cavity using talc. To summarize, we report a patient with a TB-infected giant bulla that was treated successfully with anti-TB drugs and obliteration of the pulmonary cavity using talc.